Pornographic Media and Peer’s Influence Towards Sexual Behavior among Teenagers - Murdiningsih Murdiningsih; Rosnani Rosnani; Hidayat Arifin (Universitas Airlangga, 2016)
Background: The problems associated with unsafe sexual behavior in adolescents are caused by premarital sexual intercourse with a partner of their own age. One of the problems caused by premarital sex is a pregnancy outside of marriage. Increased incidence of premarital sex is caused by the development through media depictions of sex scenes in the form of television, magazines, video clips, online media, and films. In Musi Banyuasin there are 7754 high school students, many students have dropped out of school because they get pregnant before marriage so that in adolescence their parents are forced to marry or have abortions. The aim study is determined the factors associated with unsafe sexual behavior in adolescents in high school.Method: Observational research with cross sectional and quantitative approach. The population is high school students. Sampling technique was using multistage random sampling obtained 393 samples. Bivariate analysis, chi-squareResult: the result showed a correlation between the influence of peers with adolescent sexual behavior has p-value (0,000). There was no relationship between media pornography with sexual behavior because the result more than p-value (0,05). Conclusion: Necessary to be given knowledge and assistance to adolescents about positively and creatively thing and supervision of parents to their children in order to have a friends and avoid unsafe sexual behavior.